The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2353/ajpath.2010.091082
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Triggered Lipoxin and Resolvin E1 Modulate Vascular Smooth Muscle Phenotype and Correlate with Peripheral Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the vessel wall. Recent evidence suggests that chronic vascular inflammation ensues as an imbalance between pro-and anti-inflammatory mediators. Recently identified lipid mediators (eg, lipoxins and resolvins) play active roles in promoting the resolution of inflammation. Alterations in vascular smooth muscle cell (VSMC) phenotype, which manifest as a loss of contractile protein expression and increased proliferation and migration, are prominent mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 32 publications
9
191
1
2
Order By: Relevance
“…This is of general relevance to inflammatory diseases in humans because it is sometimes difficult to obtain temporal changes in LM profiles during disease states and their resolution. 36 Nonetheless, LXA 4 levels increase during resolution of glomerulonephritis, 37 and PD1 levels are diminished in exhaled breath condensates from asthmatics. 38 Systematic mapping of cellular trafficking in a murine model of self-limited acute inflammation demonstrated that mononuclear cell accumulation at the site of inflammation occurs as part of the events that lead to the onset of resolution.…”
Section: Phagocyte Lm Signatures In Inflammation-resolution E69mentioning
confidence: 99%
“…This is of general relevance to inflammatory diseases in humans because it is sometimes difficult to obtain temporal changes in LM profiles during disease states and their resolution. 36 Nonetheless, LXA 4 levels increase during resolution of glomerulonephritis, 37 and PD1 levels are diminished in exhaled breath condensates from asthmatics. 38 Systematic mapping of cellular trafficking in a murine model of self-limited acute inflammation demonstrated that mononuclear cell accumulation at the site of inflammation occurs as part of the events that lead to the onset of resolution.…”
Section: Phagocyte Lm Signatures In Inflammation-resolution E69mentioning
confidence: 99%
“…There are few data attesting to their formation in humans based on rigorous mass spectrometric methodology. Most clinical investigations reporting the formation of SPMs rely on immunoassays ( 21 ) or MS without synthetic internal standards structurally similar to the SPMs under investigation (22)(23)(24)(25)(26)(27)(29)(30)(31)(32), often in ex vivo stimulated systems ( 17,(33)(34)(35)(36).…”
Section: Blood (Rbc Membranes) For the Study High Doses Of Lovaza Fishmentioning
confidence: 99%
“…The abnormal proliferation and migration of vascular smooth muscle cell (VSMC) are key components of various vascular diseases, including hypertension, atherosclerosis and vascular stenosis after vessel transplant [1][2][3][4]. In addition, VSMC apoptosis is one of the dominant factors that induce plaque vulnerability in atherosclerosis [5,6].…”
Section: Introductionmentioning
confidence: 99%